Association of dietary n - 3 polyunsaturated fatty acids with breast cancer risk: Serial mediating roles of erythrocyte n - 3 polyunsaturated fatty acids - Zhang, Zhuolin; Jiang, Yiling; Li, Xue; Shi, Dandan; Ma, Ting; Zhou, Ruolin; Zhang, Caixia (Frontiers in Nutrition, 2022)
Background Dietary n– 3 polyunsaturated fatty acids (PUFAs) were found to be inversely associated with breast cancer risk; however, the underlying pathways between them remain uncertain. We aimed to explore serial mediatory roles of erythrocyte n– 3 PUFAs in association between dietary n– 3 PUFAs and breast cancer risk. Materials and methods Using a case-control study, 850 cases and 861 controls completed structured questionnaires with dietary information. Erythrocyte n– 3 PUFAs were measured by gas chromatography. Odds ratios (ORs) and 95% confidence intervals (CIs) were obtained using multiple unconditional logistic regression models to examine association between dietary n– 3 PUFAs and breast cancer risk. Mediation analyses with bootstrapping were conducted to investigate indirect effects. Results Higher intake of dietary ALA, long-chain n– 3 PUFAs and total n– 3 PUFAs was associated with lower risk of breast cancer. The adjusted ORtertile 3 v.1 (95% CI) was 0.70 (0.55, 0.90) for ALA, 0.76 (0.60, 0.97) for long-chain n– 3 PUFAs and 0.74 (0.58, 0.94) for total n– 3 PUFAs, respectively. Mediation analysis showed that erythrocyte long-chain n– 3 PUFAs served as sequential mediators in the relationship between dietary long-chain or total n– 3 PUFAs and breast cancer risk. In particular, erythrocyte long-chain n– 3 PUFAs completely mediated the association between dietary long-chain n– 3 PUFAs and breast cancer risk [indirect effect (95% CI) = –0.982 (–1.529, –0.508)]. The relationship between dietary total n– 3 PUFAs and breast cancer risk was partly mediated by erythrocyte long-chain n– 3 PUFAs [indirect effect (95% CI) = –0.107 (–0.216, –0.014)], accounting for 19.31%. However, the serial mediation model in dietary ALA and risk of breast cancer was not statistically significant [indirect effect (95% CI) = –0.042 (–0.144, 0.049)]. Conclusion This study highlights the complexity and inaccuracy in using a simple analysis of individual dietary n– 3 PUFAs to examine their associations with breast cancer risk without considering the variety of metabolic processes. Interventions aimed at increasing erythrocyte long-chain n– 3 PUFAs may represent a promising strategy for breast cancer prevention.